Batna City from Organized Planning to Distortion (Case Study Biskra Road Axis - Algeria) - Dounia, Khireddine; Boudjemaa, Aichour (Mediterranean Journal of Social Sciences, 2022)
The ecological processes known to the various manifestations of visual pollution, which is defined as: every element of the physical environment is affected by changes or interventions made by man to the natural and constructed environment, which leads to its distortion and harms the public health of citizens. In order to understand its reasons for reaching a balanced urban scene and thus affecting human health. Where its features appear in various visual and visual aspects of public space, especially roads, due to the misuse of this space, which stems from wrong behaviors in addition to the lack of the planning system,which leads to emptying the architectural image of the city of its content. Received: 11 October 2021 / Accepted: 20 November 2021 / Published: 5 January 2022